ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN THE DEVELOPMENT OF MANAGEMENT PERSONNEL COMPETENCIES - Alisher MAMATOV (Scholar Express Journals, 2025)
The rapid development of digital technologies provides opportunities to organize the process of training, retraining, and upskilling personnel with innovative approaches. Considered one of the most effective technologies of the Fourth Industrial Revolution, artificial intelligence (AI) is fundamentally transforming the management of educational processes. In particular, these technologies enable the customization of education for each individual and the fulfillment of their needs on an individual basis. This article analyzes the experiences of advanced foreign countries in continuously developing the competencies of management personnel through flexible, remote, and electronic education, including the use of AI technologies. As a result of the research, the process of digitally transforming the development of competencies among management personnel active in the public service of the Republic of Uzbekistan is presented, along with the use of AI tools, the digital management of this system, and its economic efficiencies. In addition, the results of the initial diagnostic assessment of the competencies of more than 1,000 management personnel working in government agencies via an AI-based intellectual platform are analyzed, with their competencies classified according to the individual approaches required for their development
Keywords: artificial intelligence; random forest; management personnel; competence